On a Misguided Argument for the Necessity of Identity - Ari Maunu (Philosophy documentation center, 2022)
There is a certain popular argument, deriving from Ruth Barcan and Saul Kripke, from the conjunction of the Principle of the Indiscernibility of Identicals (PInI, for short) and the Principle of the Necessity of Self-Identity to the Thesis of the Necessity of Identity. My purpose is to show that this argument does not work, not at least in the form it is often presented. I also give a correct formulation of the argument and point out that PInI is not even needed in the argument for the necessity of identity.